Levels of the cancer biomarker CA 19-9 are associated with thrombin generation in plasma from treatment-naïve pancreatic cancer patients. Issue 199 (March 2021) - Mattila, N.; Hisada, Y.; Przybyla, B.; Posma, J.; Jouppila, A.; Haglund, C.; Seppänen, H.; Mackman, N.; Lassila, R.
Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is associated with a hypercoagulable state and high mortality. Increases in the plasma levels of tumor marker carbohydrate antigen (CA) 19-9 are used in diagnosis and follow-up but have also been reported to precede venous thromboembolism (VTE). Aims: We examined the association between CA 19-9 and thrombin generation (TG) in plasma from PDAC patients, as well as their association with coagulation biomarkers prior to pancreatic surgery. In addition, we determined the effect of commercial sources of CA 19-9 on TG. Methods: We collected plasma from 58 treatment-naïve PDAC patients without any signs of VTE. We measured levels of CA 19-9, FVIII, fibrinogen, D-dimer, antithrombin and extracellular vesicle (EV) tissue factor (TF) activity and TG using a Calibrated Automated Thrombogram (CAT). The effect of different commercial sources of CA 19-9 on TG in Standard Human Plasma (SHP) was also studied. Results: Patient plasma samples were divided into 4 preoperative groups based on the level of CA 19-9: none < 2, low = 3–200, high = 201–1000, and very high > 1000 U/mL. CA 19-9 levels were associated with several of the TG parameters, including endogenous thrombin potential, peak, and time to peak. CA 19-9 did not associate with any of the coagulation biomarkers. Spiking of SHP with CA 19-9 increased TG but this was decreased by an anti-TF antibody. Conclusions: CA 19-9 was associated with TG in patients prior to any pancreatic cancer treatments or signs of VTE. Some commercial sources of CA 19-9 enhanced TG in SHP seemingly due to contaminating TF. Highlights: CA 19-9 and thrombin generation are associated in pancreatic cancer patients. CA 19-9 in patient samples did not associate with coagulation biomarkers. Some commercial CA 19-9 sources are contaminated with tissue factor.